The Association between Nutrition Education Based on Local Wisdom with Family Nutrition Knowledge in West Lombok, Indonesia - Wulandari Dewi Susilawati; Muhammad Nawawi; Musparlin Halid (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2026)
Introduction: In West Lombok Regency, particularly in Rumak Village, Kediri, there are various traditional practices related to food and health that have been passed down from generation to generation. These practices reflect local understanding of nutrition and health, which can be used as a basis for designing educational approaches that are more relevant and acceptable to the community. The study aims to analyse factors related to the level of family nutrition knowledge through a local wisdom-based nutrition education approach. Methods: This study used a cross-sectional design involving 263 family respondents selected proportionally in Rumak Village, West Lombok. Analysis was performed using Chi-square tests and logistic regression to determine the dominant factors associated with family nutrition knowledge. Results: The study results indicate that of the 263 respondents, 60.5% had good nutritional knowledge. The analysis results show that there was a significant association between gender (p=0.004), highest level of education (p=0.012), employment (p=0.002), income (p=0.002), source of nutritional information (p=0.019), frequency of attending local nutrition education (p=0.031), suitability of materials to local culture (p=0.001), active family participation (p=0.029), and understanding of local nutrition messages (p=0.001) with family nutrition knowledge. Furthermore, family understanding of local nutrition messages (p=0.001) was the most dominant factor influencing family nutrition knowledge. Conclusions: Nutrition education based on local wisdom has proven to play an important role in improving family nutrition knowledge. These findings indicate that nutrition education tailored to local culture and involving active family participation is an effective strategy for sustainably improving community nutrition knowledge.